Images of Rome in Polish and Serbian literature of the Romantic Period - Ewertowski, Tomasz (КарГУ, 2013)
The main aim of the paper is to analyze and interpret various images of Rome in Polish and Serbian literature of the Romantic period. The main concepts are based on imaginary geography. Michael Foucault's concept of heterotopia is also used. The primary focus of the paper is the literary works of the following Serbian and Polish authors: P. Njegoš, L. Nenadović, A. Mickiewicz, J. Słowacki, Z. Krasinski, C. Norwid. It corroborates how various philosophical ideas and ideological values are demonstrated in representations of the ruins of Rome.

Głównym celem artykułu jest analiza i interpretacja różnych obrazów Rzymu w polskiej i serbskie literaturze okresu romantyzmu
Keywords: Rome; Romantic period; Słowacki; Krasiński; Mickiewicz; Njegoš; Nenadović; imaginary geography; Rzym; Rim; romantyzm; romantizam; travel writing; podróżopisarstwo; putopis; geografia wyobrażona; imaginarna geografija